AKTIVITAS ANTIOKSIDAN EKSTRAK METANOL DAUN KELENGKENG (Euphoria longan (L) Steud.) DENGAN METODE PENANGKAPAN RADIKAL 2,2’-DIFENIL-1-PIKRILHIDRAZIL - Nina Salamah; Erlinda Widyasari (Universitas Ahmad Dahlan, 2015)
The degenerative diseases is caused by endogenous antioxidant cannot neutraliced from increased concentration of free radicals, therefore it is necessary to consume antioxidant from the outside ofbody for neutralizing and destroying free radicals. The aim of this research is to evaluate the antioxidant activity of methanolic extract of longan leaves. The experiment of antioxidant activity from extract longan leaves uses the scavenging assay using 2,2’-diphenyl-1-pycrylhydrazyl (DPPH) method and quersetin as positive control. The analytical result is processed using linear regression methode in order to get ES50 value. The results of research showed that theincreasing concentration of methanolic extract, and quercetin causes the higher percentage of DPPH radical scavenging. The ES50 values of methanolic extract and quercetin obtained are 40.32 µg/ml and 2.48 µg/ml respectively.